1986
DOI: 10.1111/j.1600-0447.1986.tb06243.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality in depression: concordance between clinical assessment and questionnaires

Abstract: The concordance between Vanggaard's concept of character neurosis and three personality questionnaires (Marke-Nyman Temperament Scale, Cesarec-Marke Personality Scale, and Eysenck Personality Questionnaire) was evaluated in 73 patients who were treated for a major depression in general practice. After an interview with the patients Vanggaard classified 57 of them to be without character neurosis, and the remaining 16 patients were considered to have a character neurosis. It was found that Eysenck's Neuroticism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…We have found Eysenck's neuroticism scale the most useful self-rating scale for personality dimen sions [Bech et al, 1986b], It is of interest that Waters [1986], in his intensive studies on headache, has found the following nine items relevant for describing neurotic per sonality: Do you wear yourself out worrying about your health? ; Do you suffer from se vere nervous exhaustion?…”
Section: Personalitymentioning
confidence: 95%
“…We have found Eysenck's neuroticism scale the most useful self-rating scale for personality dimen sions [Bech et al, 1986b], It is of interest that Waters [1986], in his intensive studies on headache, has found the following nine items relevant for describing neurotic per sonality: Do you wear yourself out worrying about your health? ; Do you suffer from se vere nervous exhaustion?…”
Section: Personalitymentioning
confidence: 95%
“…The associations between depression and the dimensions of extraversion and neuroticism have been assessed in various studies in students [Clarke, 2004;Hepburn and Eysenck, 1989;McCleery and Goodwin, 2001;Saklofske et al, 1995;Williams, 1990], in family members of patients with depression [Duggan et al, 1995;Katz and McGuffin, 1987], in twins [Kendler et al, 1993b], in other nonclinical settings [Boyce et al, 1991;Christie and Venables, 1973;Farmer et al, 2002], and in clinical settings [Bech et al, 1986;Berlanga et al, 1999;Boyce and Parker, 1985;Coppen and Metcalfe, 1965;Cuijpers et al, 2005;Duggan et al, 1991;Garside et al, 1970;Julian et al, 1969;Kendell and DiScipio, 1968;Ranjith et al, 2005;Ulusahin and Ulug, 1997;Weissman et al, 1978] but rarely in the general population [Bienvenu et al, 2004;Cox et al, 2004]. In addition, researchers have investigated the dimensions of extraversion and neuroticism (with an abbreviated scale) in the general population in one study [Goodwin et al, 2002], and the dimension of neuroticism alone in twins [Fanous et al, 2002;Kendler et al, 1993aKendler et al, , 2002Kendler et al, , 2004Roberts and Kendler, 1999], in relatives of depressive patients [Sham et al, 2000], and in the general population [de Graaf et al, 2002;Henderson et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Originally proposed by Eysenck, neuroticism reflects the level of emotional stability of the individual, which at one extreme can manifest itself as anxiety, depression, and other moody behaviors [Eysenck and Eysenck, 1975;Kendler et al, 1993;Cloninger, 1994]. Numerous studies have examined the relationship between neuroticism and major depressive disorder (MDD) and have determined that individuals who have episodes of depression have higher levels of neuroticism [McGuire et al, 1963;Hirschfeld and Klerman, 1979;Bech et al, 1986]. Second, the association appears to be causal.…”
Section: Introductionmentioning
confidence: 99%